Work after retirement: worklife transitions of career public employees. (10th July 2021) - Clark, Robert L.; Hammond, Robert G.; Liu, Siyan
Abstract: Engaging in paid employment after claiming retirement benefits may be an important avenue for individuals to work longer as life expectancies rise. After separating from one's career employer, individuals may engage in paid work to stay active or to supplement their current level of retirement savings or both. Individuals who choose not to work after claiming may be expressing their preference to stay retired, perhaps because their retirement income is sufficient. However, the decision to work after claiming may be driven by the lack of retirement planning and insufficient savings, while the lack of post-claiming work may reflect the inability to find adequate employment opportunities. We use administrative records merged with panel data from several surveys of public employees in North Carolina to study the decision to engage in paid work after claiming retirement benefits. More than 60% of active workers plan to work after claiming benefits, while only around 42% of the same sample of individuals have engaged in post-claiming paid work in the first few years after leaving public sector employment. Despite this gap, stated work plans are strongly predictive of actual post-claiming work behavior. Our final analysis uses self-reported measures to gauge the financial well-being of our sample in the early years after leaving career employment.